Oxygen‐deficient water zones in the Baltic Sea promote uncharacterized Hg methylating microorganisms in underlying sediments. Issue 1 (18th November 2021) - Capo, Eric; Broman, Elias; Bonaglia, Stefano; Bravo, Andrea G.; Bertilsson, Stefan; Soerensen, Anne L.; Pinhassi, Jarone; Lundin, Daniel; Buck, Moritz; Hall, Per O. J.; Nascimento, Francisco J. A.; Björn, Erik
Abstract: Human‐induced expansion of oxygen‐deficient zones can have dramatic impacts on marine systems and its resident biota. One example is the formation of the potent neurotoxic methylmercury (MeHg) that is mediated by microbial methylation of inorganic divalent Hg (Hg II ) under oxygen‐deficient conditions. A negative consequence of the expansion of oxygen‐deficient zones could be an increase in MeHg production due to shifts in microbial communities in favor of microorganisms methylating Hg. There is, however, limited knowledge about Hg‐methylating microbes, i.e., those carrying hgc genes critical for mediating the process, from marine sediments. Here, we aim to study the presence of hgc genes and transcripts in metagenomes and metatranscriptomes from four surface sediments with contrasting concentrations of oxygen and sulfide in the Baltic Sea. We show that potential Hg methylators differed among sediments depending on redox conditions. Sediments with an oxygenated surface featured hgc ‐like genes and transcripts predominantly associated with uncultured Desulfobacterota (OalgD group) and Desulfobacterales (including Desulfobacula sp.) while sediments with a hypoxic‐anoxic surface included hgc ‐carrying Verrucomicrobia, unclassified Desulfobacterales, Desulfatiglandales, and uncharacterized microbes. Our data suggest that the expansion of oxygen‐deficient zones in marine systems may lead to a compositional change of Hg‐methylating microbial groups in the sediments, where Hg methylators whose metabolism and biology have not yet been characterized will be promoted and expand.